An Ns1abp-like gene promotes white spot syndrome virus infection by interacting with the viral envelope protein VP28 in red claw crayfish Cherax quadricarinatus. (July 2018) - Xie, Xiao-lu; Chang, Xue-jiao; Gao, Yan; Li, Dong-li; Liu, Ling-ke; Liu, Man-jun; Wang, Ke-jian; Liu, Hai-peng
Abstract: Influenza A virus non-structural-1A binding protein (named as Ns1abp) was originally identified as a host protein from human that bound to the viral NS-1 protein. In our previous study, the expression of an Ns1abp-like gene (denoted as CqNs1abp-like gene) was found to be up-regulated in a transcriptome library from the haematopoietic tissue (Hpt) cells of red claw crayfish Cherax quadricarinatus post white spot syndrome virus (WSSV) infection. To elucidate the role of CqNs1abp-like gene involved in WSSV infection, we cloned the CqNs1abp-like gene in which the open reading frame was 2232 bp, encoding 743 amino acids with two typical domains of one BTB (Broad-Complex, Tramtrack and Bric a brac) domain at N-terminal and six Kelch domains at C-terminal. The gene expression profile showed that the mRNA transcript of CqNs1abp-like gene was widely expressed in all the tested tissues with highest expression in nerve, relatively high expression in Hpt and lowest expression in eyestalk. Importantly, both the WSSV entry and the viral replication were significantly reduced in Hpt cells after gene silencing of CqNs1abp-like gene. By using protein pull-down assay, we found that the recombinant BTB domain, six Kelch domains and CqNs1abp-like intact protein were all bound to the WSSV envelope protein VP28, respectively, in which the BTB domain showed slightly less binding affinity than that of the six Kelch domains or the recombinant intact protein. Besides, the WSSV entry into Hpt cells was clearly decreased when the virus was pre-incubated with the recombinant BTB domain, six Kelch domains, or the recombinant CqNs1abp-like intact protein, respectively, suggesting that the CqNs1abp-like gene was likely to function as a putative recognition molecular towards WSSV infection in a crustacean C. quadricarinatus. Taken together, these data shed new light on the mechanism of WSSV infection and a putatively novel target on anti-WSSV infection in crustacean farming. Highlights: Loss-of-function of CqNs1abp-like gene clearly reduced the WSSV entry and replication in Hpt cells. The recombinant BTB, six Kelch domains and intact proteins were all bound to the envelope protein VP28, respectively. The WSSV entry was decreased if pre-incubated with the recombinant BTB, six Kelch domains, or the intact protein.